OVERCOMING CULTURAL SHOCK AMONG INTERNATIONAL STUDENTS - Nakonechna, Lyubov (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
The article discusses the role of digital innovations in teaching foreign languages at different skill levels and their measurements in various spheres of real social action. An effective assessment tool for students’ achievements is the Lafleur matrix, based on the concept of the standardized scale for measuring language proficiency levels (CEFR). This approach enhances the objectivity and accuracy of the assessment process by considering various aspects of language learning, including literacy levels, structural components, and language functions, which are key dimensions of language instruction and learning. It provides a systematic approach to evaluating knowledge levels and individual student achievements, serving as a basis for identifying and addressing their educational needs. Emphasis is placed on the utility of such standardized assessment methodologies, particularly in an international context, where students from different countries can be evaluated against the same criteria. This helps avoid inconsistencies in their interpretations of assessments, as it establishes a basis for comparing knowledge levels among different student groups, thereby increasing the objectivity and effectiveness of the assessment process. It creates a stable foundation for the development of the education system as a whole. ______________ References: • Conseil de l’Europe. Cadre européen commun de référence pour les langues – Apprendre, enseigner, évaluer (Didier, 2001). • Conseil de l’Europe. (2018). Cadre européen commun de référence pour les langues – Apprendre, enseigner, évaluer. Vol.: Complémentaire avec de nouveaux descripteurs: Programme des Politiques linguistiques (Division des Politiques éducatives. Service de l’Éducation, 2018). • Conseil de l’Europe. Cadre européen commun de référence pour les langues – Apprendre, enseigner, évaluer. Volume complémentaire: Programme des Politiques linguistiques (Division des Politiques éducatives. Service de l’Éducation, 2021). • Houssaye, Théorie et pratiques de l’éducation scolaire (I) – Le triangle pédagogique (Peter Lang, 1988). • Houssaye, Théorie et pratiques de l’éducation scolaire, 3e éd. (Peter Lang, 2000). • Faerber, R. Le groupe d’apprentissage en formation à distance : ses caractéristiques dans un environnement virtuel. In La place des TIC en formation initiale et continue, F. Larose, T. Karsenti (Éds.) (Éditions du CRP, 2002): 99-128. URL: https://www.researchgate.net/publication/267553983_La_place_des_TIC_en_formation_initiale_et_continue • Lafleur, F. (2022). Les pratiques émergentes à privilégier en contexte d’enseignement comodal au secteur des jeunes. Rapport de recherche-action-formation préparé pour le ministère de l’Éducation du Québec (MÉQ) – Phase II. (Gouvernement du Québec? 2022). URL: https://www.education.gouv.qc.ca/fileadmin/site_web/documents/ education/PAN_ Pratiques-emergentes-contexte-comodal-phase2.pdf • Jakobson, Les fondations du langage – Essais de linguistique générale (N. Ruwet, trad. et préface) (1963). URL: http://www.leseditionsdeminuit.fr/livre-Fondations_du_langage._ Essais_de_linguistique_g%C3%A9n%C3%A9rale_I%C2%A0_(Les)-2137-1-1-0-1.html • Parsons, T., Shils, E. Toward a General Theory of Action (Harvard University Press, 1951). URL: https://www.degruyter.com/document/doi/10.4159/harvard.9780674863507/html